Immunological and Diagnostic Features of Pulmonary Tuberculosis with Allergic Bronchitis - Farhadovna Khasanova, Mokhira (Journal of Neonatal Surgery, 2025)
Patients with pulmonary tuberculosis (TB) often experience simultaneous presentation of chronic allergic bronchitis which creates difficulties for proper diagnosis and medical treatment. The immune response in TB incorporates Th1 elements but allergic bronchitis runs on Th2 mechanisms which results in systemic immune dysregulation. The widespread coexistence of these conditions in Central Asia currently lacks adequate scientific research about their immunological aspects along with diagnostic complexity. The research analyzed pulmonary hypertension patients with chronic allergic disease and tuberculosis from Khorezm Regional Multidisciplinary Hospital. The research team performed clinical tests alongside laboratory examinations and Computed Tomography imaging and Echocardiography procedures and immunological evaluations. Patients participated in the Seattle Questionnaire to gauge physical activity levels and emotional stability and professional adaptation before bosentan and sildenafil therapy and after conclusion of the study. The study revealed 10.5% of patients presented with pulmonary hypertension that mainly started from left ventricular dysfunction (78.7%) and respiratory disorders (9.7%). Patients with TB and allergic bronchitis had simultaneous inflammatory problems and disturbed cytokine levels which decreased the success of their therapy. The research showed a notable drop in physical activity levels together with emotional steadiness which demonstrated the necessity to develop better diagnostic methods for clinical purposes. The correct diagnosis of TB and allergic bronchitis requires specific immunological strategies and enhancement of therapeutic strategies. The medical use of Bosentan along with sildenafil showed success in treating pulmonary hypertension but immune-modulating therapies need to be systematically implemented. The study shows that diagnostic protocols must incorporate immunological markers to achieve better disease separation and treatment success. Researchers need to develop individualized therapeutic approaches to address patients who suffer from both TB and allergic bronchitis